Analysis of Thai Undergraduates' Control of a Generic Structure in Discussion Essays - Saowadee Kongpetch (University of Muhammadiyah Prof. DR. HAMKA, 2021)
This study analyzed a generic structure in 15 discussion essays written by 15 third year English majors in one public university in the northeast of Thailand. It aimed to find out the extent to which the students were aware of a generic structure typical of a discussion genre and were able to utilize it to construct their essays. Drawing on the works of Sydney genre theorists (e.g. Knapp, 1989; Knapp and Watkins, 1994), the analysis results revealed that most students had a good control of the generic structure because their essays exhibited all three major elements as expected of a discussion genre, namely Issue, Arguments for and against, and Recommendation. Nevertheless, a closer inspection showed that some essays were not as successful as the others. While most were able to write Issue and Recommendation well, their development of Arguments needs to be considerably improved. The study concluded that the students' ability to execute a generic structure typical of a genre and to develop effective arguments are crucially important for the quality and persuasiveness of a discussion essay. Key words: discussion essays, generic structure, issue, arguments, recommendation